2019
DOI: 10.35118/apjmbb.2019.027.3.11
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of signal peptides for secretory production of a-amylase in Bacillus subtilis

Abstract: α-Amylases are important commercial enzymes and have a broad application in industrial processes and medicine. Gram-positive bacteria such as Bacillus subtilis are possible host organisms for α-amylases secretory production. Secretion of α-amylases to the culture medium versus intracellular production has several advantages such as prevention of inclusion bodies accumulation, higher product stability and solubility. Signal peptides are considered as one of the most essential elements for successful secretory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The level of recombinant protein expression could be enhanced by selecting an efficient signal peptide 56,59,60 . For example, in a study by Chen et al 57 .…”
Section: Expression Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of recombinant protein expression could be enhanced by selecting an efficient signal peptide 56,59,60 . For example, in a study by Chen et al 57 .…”
Section: Expression Hostsmentioning
confidence: 99%
“…The level of recombinant protein expression could be enhanced by selecting an efficient signal peptide. 56,59,60 For example, in a study by Chen et al 57 showed that the nprE that originated from B. subtilis has a higher efficiency than other types in the production of recombinant α-amylase.…”
Section: Signal Peptide and Secretory Pathwaymentioning
confidence: 99%
“…All contained only a Glyc_debranch-domain, responsible for hydrolytic glycogen debranching in starch granules (Nakayama et al, 2001). All sequences in this group were without signal peptide indicating intracellular enzyme activity for glycogen turnover (Jespersen et al, 1993;Asadi et al, 2019).…”
Section: *Weak Signalmentioning
confidence: 99%